The Influence of Learning Models and Learning Motivation on English Grammar Skills (Experiment at Private Vocational Schools in Cilegon) - Mutmainah, Mutmainah; Purnama, Syahfitri; Suseno, Imam (INFERENCE: Journal of English Language Teaching, 2024)
This study aims to analyze the effect of the jigsaw learning model and students' learning motivation on their skill of English grammar. A quantitative approach with an experimental method was employed in this research. The research sample consisted of 60 students of 12th-grade from a high school in Cilegon. Data were collected using grammar tests and student learning motivation questionnaires. Data analysis was conducted using two-way ANOVA. The results revealed that the jigsaw learning model significantly improved students' grammar skills compared to conventional teaching methods. Students with high learning motivation showed greater improvement in grammar proficiency than those with low motivation. Moreover, an interaction was found between the jigsaw learning model and students' learning motivation. The implications of this study highlight the importance of applying models jigsaw in classrooms to improve grammar skill, particularly in grammar. It also emphasizes the need for teachers to understand the critical role of student motivation in supporting successful learning.